Does neuromotor immaturity represents a risk for acquiring basic academic skills in school-age children? - Ivanović Lidija B.; Ilić-Stošović Danijela; Nikolić Snežana; Medenica Veselin (Vojnosanitetski Pregled)
Background/Aim. Studies that investigated the presence of soft neurological signs in terms of neuromotor immaturity and impact on the ability of reading, writing and calculation are rare. At school age, cognitive development in children of the typical population is monitored over, while much less was focused on motor development. This is one of the important reasons for conducting this research. The aim of this study is to determine whether neuromotor immaturity of children poses a risk for the adoption of the basic academic skills in school children. Most authors investigated the presence of dysgraphia, dyslexia and dyscalculia in clinically diagnosed conditions. Methods. The data were obtained by testing. To assess neuromotor maturity, The Developmental Screening Test was used. The quality of handwriting was evaluated according to the criteria proposed by Simner and Eidlitz. Quality of reading skills is assessed by the Three-dimensional Reading Test. Evaluation of the presence of difficulties in numeracy was performed by a series of adapted tasks, taken from the Romanian Screening Instrument for Dyscalculia. Results. The sample was divided into two groups of pupils according to the results. The groups consisted of students with and without the presence of neuromotor immaturity. There was a significantly higher prevalence of students with difficulties in reading, writing and numeracy in the group of neuromotor immature students. Conclusion. The results clearly indicated that neuromotor immaturity of children represents a risk to the adoption of the basic academic skills in children in school age. We believe that the school age is very important time to monitor motor development of a child to the same extent as the cognitive development. In this way, we would have the opportunity to intervene on time and reduce a possibility of school failure. Wider studies in this area are urgently needed.